Intestinal intussusception and progressive anemia due to pyogenic granuloma of the ileum: a case report - Kodai Nagakari; Akikazu Yago; Yu Ohkura; Daisuke Tomita; Shusuke Haruta; Yutaka Takazawa; Masaki Ueno (Surgical Case Reports)
Abstract Background Pyogenic granuloma is a benign vascular tumor, usually occurring on the skin or in the oral cavity. Small intestinal pyogenic granuloma is extremely rare, but intestinal intussusception due to the tumor is even rarer. Only 3 cases have been reported in the English literature at this writing. Case presentation An 86-year-old woman presented with abdominal pain and vomiting. Laboratory data discovered anemia. Contrast-enhanced computed tomography revealed small bowel obstruction due to intestinal intussusception. After decompression by long tube for 1 week, the obstruction did not improve and the anemia got worse. Therefore, laparoscopic assisted small bowel resection was performed as a diagnostic therapy. Pathology confirmed the diagnosis of pyogenic granuloma. The postoperative course was uneventful and the patient was discharged 10 days after surgery. Conclusions We experienced a case of intestinal intussusception and progressive anemia due to pyogenic granuloma of the ileum. Although the condition is extremely rare, surgeons must take into consideration the tumor in similar cases, and complete surgical resection is required.